Understanding Pornography Access Behavior Among Children and Adolescents with Disabilities: A Mixed-Methods Study - Nurtarisa; Prahastuti, Nurul Fajriyah; Harfi Alfiah; Umi Kholifah (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2023)
This study aims to explore the behavior of children and adolescents with disabilities in accessing pornography at the SLB Negeri 1 Panjatan Dormitory, Kulon Progo. Children and adolescents with disabilities face challenges in cognitive development, including understanding sexual issues, which is further exacerbated by heightened curiosity during puberty. This research employs a mixed-method approach, combining quantitative methods through questionnaires and qualitative methods through in-depth interviews, observation, and documentation. The results show that 69% of respondents exhibit moderate levels of behavior in accessing pornography, which aligns with previous literature on the vulnerability of cognitively impaired children to inappropriate content. The study also reveals no significant difference between males and females in this behavior, contrasting with findings in the general population where males tend to be more dominant. The primary reason for accessing pornography is curiosity, compounded by limited access to appropriate reproductive health education. Furthermore, peers play a crucial role in providing information about accessing pornography, with 69% of respondents stating they received such information from their friends. These findings highlight the need for interventions through proper sex education, social environment supervision, and controlled access to technology to mitigate the negative impacts of pornography exposure on children and adolescents with disabilities. Keywords: pornography access behavior, children and adolescents with disabilities, sex education, peer influence, cognitive limitations.   Penelitian ini bertujuan untuk mengeksplorasi perilaku anak dan remaja penyandang disabilitas dalam mengakses pornografi di Asrama SLB Negeri 1 Panjatan, Kulon Progo. Anak-anak dan remaja penyandang disabilitas menghadapi tantangan dalam perkembangan kognitif, termasuk dalam memahami isu-isu seksual, yang diperparah dengan rasa ingin tahu yang tinggi selama masa pubertas. Penelitian ini menggunakan metode campuran (mix methods), dengan pendekatan kuantitatif melalui kuesioner dan pendekatan kualitatif melalui wawancara mendalam, observasi, serta dokumentasi. Hasil penelitian menunjukkan bahwa 69% responden berada pada kategori sedang dalam perilaku mengakses pornografi, yang sejalan dengan literatur sebelumnya tentang kerentanan anak-anak dengan keterbatasan kognitif terhadap konten yang tidak pantas. Penelitian ini juga mengungkap bahwa tidak ada perbedaan signifikan antara laki-laki dan perempuan dalam perilaku ini, berbeda dengan temuan di populasi umum yang menunjukkan kecenderungan laki-laki lebih dominan. Alasan utama mengakses pornografi adalah rasa penasaran, yang diperkuat oleh kurangnya akses terhadap pendidikan kesehatan reproduksi yang sesuai. Selain itu, teman sebaya menjadi faktor utama dalam memberikan informasi mengenai akses pornografi, dengan 69% responden mengaku mendapatkannya dari teman. Temuan ini menekankan perlunya intervensi melalui pendidikan seks yang tepat, pengawasan lingkungan sosial, serta kontrol terhadap akses teknologi untuk mengurangi dampak negatif dari paparan konten pornografi pada anak dan remaja penyandang disabilitas. Kata kunci: perilaku mengakses pornografi, anak dan remaja penyandang disabilitas, pendidikan seks, teman sebaya, keterbatasan kognitif.